Phytochemical Screening and Antioxidant Activity of Dyera polyphylla (Miq) Steenis Extract Using the DPPH Method - Putri Dharma Monika; Rini Muharini; Eni Mayasari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This research aimed to determine the chemical profile and antioxidant activity of the jelutung rawa plant (Dyera polyphylla). Phytochemical screening tests were conducted using specific reagents, thin-layer chromatography (TLC), and high-performance liquid chromatography (HPLC). Determination of antioxidant activity was performed the DPPH method. The research results showed the presence of secondary metabolite compounds, namely alkaloids, flavonoids, phenolics, tannins, and terpenoids in the leaves, while the contain alkaloids, phenolics, tannins, and terpenoids. The antioxidant activity in this plant has been identified as a strong natural antioxidant.